Akkermansia muciniphila in neurological disorders: mechanisms and therapeutic potential via the gut-brain axis - Feng, Jingzhi; Hu, Xiaomin; Liu, Jiancheng; Wang, Wenchun; Chen, Liuyi; Pang, Rizhao; Zhang, Anren (Frontiers in Neuroscience, 2025)
In recent years, the role of Akkermansia muciniphila (A. muciniphila) in neurological diseases has attracted increasing attention. As a probiotic, A. muciniphila is closely associated with host health, metabolism, and immunity, demonstrating therapeutic potential in various conditions such as obesity, atherosclerosis, inflammatory bowel disease, diabetes, and liver disorders. In the context of neurological diseases, A. muciniphila significantly influences the host brain through the microbiota–gut–brain axis (MGBA). This review summarizes the roles and mechanisms of A. muciniphila and its active components (e.g., the outer membrane protein Amuc_1100, extracellular vesicles AmEVs, and short-chain fatty acids SCFAs) in various neurological disorders, including Alzheimer’s disease (AD), Parkinson’s disease (PD), depression, cerebral palsy (CP), epilepsy (EP), autism spectrum disorder (ASD), and amyotrophic lateral sclerosis (ALS). It exerts protective effects by enhancing the intestinal barrier, regulating lipid metabolism, producing SCFAs, secreting neuroactive substances, and inhibiting neuroinflammation, thereby suggesting novel therapeutic avenues for neurological disorders. However, due to limited data from large-scale human clinical trials and the complexity of disease mechanisms and host–microbiota interactions, its clinical translation faces considerable challenges. Future efforts should focus on multicenter randomized controlled trials and in-depth mechanistic studies utilizing technologies such as metabolomics to facilitate evidence-based clinical application.